How does a sustainable ocean economy affect national GDP? - Ngan Bich Nguyen (Cogent Economics & Finance, 2024)
A sustainable ocean economy, or blue economy, encompasses economic activities utilizing marine resources while prioritizing the long-term health of oceans. While its potential to contribute to Gross Domestic Product (GDP) is acknowledged, limited research explores its specific influence on national economic performance. This study investigates how a sustainable ocean economy impacts GDP by examining the balance between economic development and environmental stewardship. Through literature review and empirical analysis, four key sectors-sustainable fisheries, marine biotechnology, renewable energy, and government policies-are identified as significant contributors to GDP. The study also highlights the role of open trade in boosting economic growth. Findings indicate that well-managed sustainable ocean economies enhance GDP, promote social well-being, and strengthen environmental resilience. The research emphasizes the necessity of integrated policy frameworks that support sustainable practices and investments in marine resources. By underscoring the blue economy's potential as a driver of economic development, this study advances current literature and advocates for its pivotal role in fostering national prosperity and sustainability. This research examines the critical relationship between a sustainable ocean economy and national GDP, offering insights into how sustainable practices in marine resource utilization drive economic growth. By identifying key sectors such as sustainable fisheries, marine biotechnology, renewable energy, and government policies, the study highlights their significant contributions to GDP while emphasizing the value of open trade in boosting economic performance. The findings underscore the importance of an integrated policy framework to balance economic development with environmental stewardship. This work not only advances the understanding of the blue economy's potential but also provides actionable recommendations for policymakers to harness its power as a driver of national prosperity and sustainability, ensuring long-term socio-economic and environmental resilience.
Keywords: 330; government's policy; Gross Domestic Product; marine biotechnology; renewable energy; sustainable fisheries; Sustainable ocean economy